2003
DOI: 10.1038/sj.bjc.6601430
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between catalase gene therapy and the cardioprotector monohydroxyethylrutoside (MonoHER) in protecting against doxorubicin-induced cardiotoxicity in vitro

Abstract: Cardiotoxicity is the main dose-limiting side effect of doxorubicin in the clinic. Being a free radical producer, doxorubicin affects the heart specifically because of its low antioxidant capacity. Among those antioxidants, catalase is present in very low levels in the heart compared to other organs. Since catalase is an essential enzyme in detoxifying hydrogen peroxide, the aim of the present study was to investigate the protective effect of catalase as delivered by an adenovirus vector against doxorubicin-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The observed cardiotoxic effects of DOX on H9C2 and primary neonatal cardiomyocytes are in agreement with reported data. 21,22 The mechanism of DOX on these cells has been attributed to the induction of apoptosis mediated by the intrinsic signaling cascade, resulting in mitochondrial dysfunction and myofibrillar degeneration. 21,[23][24][25] We have demonstrated DOX-induced apoptosis in H9C2 cells, as indicated by the increase in annexin V staining and expression of active caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…The observed cardiotoxic effects of DOX on H9C2 and primary neonatal cardiomyocytes are in agreement with reported data. 21,22 The mechanism of DOX on these cells has been attributed to the induction of apoptosis mediated by the intrinsic signaling cascade, resulting in mitochondrial dysfunction and myofibrillar degeneration. 21,[23][24][25] We have demonstrated DOX-induced apoptosis in H9C2 cells, as indicated by the increase in annexin V staining and expression of active caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, the serum levels of the antioxidants required for cardioprotection were not pharmacologically achievable (253), while in others the cardioprotectants yielded a reduction in the anticancer efficacy of doxorubicin (30,31,230). Tissue uptake of the antioxidants, whether small molecule or gene therapy based, has also limited the clinical development of general free radical scavengers (1,2,151,253).…”
Section: Iron Chelators As Cardioprotective Agentsmentioning
confidence: 99%
“…General antioxidant strategies such as with coenzyme Q, vitamin A, carotenoids, vitamin C, vitamin E, flavonoids, polyphenols, n-acetyl cysteine, catalase, or superoxide dismutase gene therapies have been tested for their ability to ameliorate anthracycline-induced cardiotoxicity (1,2,11,151,181,206,218,253,282). Early in vitro and preclinical studies with several antioxidants showed promising cardioprotection that did not translate into clinical efficacy (31,151,230,282).…”
Section: Iron Chelators As Cardioprotective Agentsmentioning
confidence: 99%
“…Due to the presence of less developed antioxidant defence mechanisms, heart is particularly vulnerable to injury by anthracycline -induced reactive oxygen species [8]. Antioxidants have been reported to have beneficial effects against DOX-induced cardiotoxicity in mice and rats [9] as they protect cells and tissues from free radicals induced oxidative damage and injury [10].…”
Section: Introductionmentioning
confidence: 99%